2021
DOI: 10.1016/j.scitotenv.2020.141575
|View full text |Cite
|
Sign up to set email alerts
|

Competing PM2.5 and NO2 holiday effects in the Beijing area vary locally due to differences in residential coal burning and traffic patterns

Abstract: The holiday effect is a useful tool to estimate the impact on air pollution due to changes in human activities. In this study, we assessed the variations in concentrations of fine particulate matter (PM 2.5 ) and nitrogen dioxide (NO 2 ) during the holidays in the heating season from 2014 to 2018 based on daily surface air quality monitoring measurements in Beijing. A Generalized Additive Model (GAM) is used to analyze pollutant concentrations for 34 sites by compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…The seasonal factors are therefore mostly related to humid weather conditions. As reported in a related study ( Hua et al, 2021b ), the opposite holiday effects of NO 2 and PM 2.5 were also observed. The interannual trends suggested that long-term control policies contributed to reductions of 26% for NO 2 and 46% for PM 2.5 from 2015 to 2020 during January to June.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…The seasonal factors are therefore mostly related to humid weather conditions. As reported in a related study ( Hua et al, 2021b ), the opposite holiday effects of NO 2 and PM 2.5 were also observed. The interannual trends suggested that long-term control policies contributed to reductions of 26% for NO 2 and 46% for PM 2.5 from 2015 to 2020 during January to June.…”
Section: Resultssupporting
confidence: 80%
“…The limit of model performance is determined by the uncertainty in the meteorology dataset, for example uncertainties in the simulation of the boundary layer height. The r 2 was somewhat lower and RMSE was somewhat higher for the hourly models than for the daily models ( Hua et al, 2021b ) mainly due to the high variability of hourly measurements and the greater difficulty in simulating the diurnal profiles. The lower model performance for the sites located in rural areas relative to the sites located in downtown and suburban can be seen in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the new year approaches, factories shut down and release their workers so they can travel home and spend time with their families during the Spring Festival (which was 24–30 January 2020) [ 25 ]. Besides, most industrial plants remain closed until the end of the holiday [ 26 ].…”
Section: Data and Empirical Methodologymentioning
confidence: 99%